PERSPEKTIF AGRIBISNIS KAKAO DI SULAWESI TENGGARA (Studi kasus Kabupaten Kolaka) - DARWIS, VALERIANA; AGUSTIN, NUR KHOIRIYAH (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005, 2012)
Disease-pest attack is extremely affected cocoa harvesting. This paper also study cocoa agribusiness in Kolaka District, South-East Sulawesi which focused on production, price, marketing and institution aspects. The result shows production reduced 40 – 50 percent because of disease-pest attack, there is no price differentiation on fermented cocoa and unfermented cocoa, price transformation faster received to farmer when cocoa price reduced, the farmers which near subdistrict market are more free to sell their cocoa, and the farmer less access to inventory cooperative.
Keywords: Perspective, Agribusiness, Cocoa